(untitled) (Bangladesh Journal of Plant Taxonomy, 2013)
Amid serious concerns over declining taxonomic research world-wide, Bangladesh showed positive trends over 1972-2002. Some important developments in the global arena over the last decade give a mixed view on the growth of taxonomic research. This demands revisiting Bangladeshs plant taxonomic research to identify major factors guiding its courses. Taxonomic papers published in three Bangladeshi journals and the Flora of Bangladesh (1972-2012) were analyzed using a scoring system. The present study reveals a four-fold increase in annual average of integrated taxonomic studies (those use knowledge of other branches of biology) over the last decade compared with the preceding decade. Conventional, inventory type taxonomic studies, on the other hand, has reduced by 15%. Studies on algae showed 42% increase in annual average, while studies on angiosperms remained unchanged. Although unpublished researches like Masters theses increased significantly in recent years, the number of published work has decreased. The possible reasons for such decline are no net increase in plant taxonomists over the last decade, taxonomists struggling to transform researches into publishable manuscripts, and enhanced reputation of Bangladeshi journals increasing the proportion of foreign papers (a situation termed as reputational backlash). The paper envisages that classical taxonomic studies will dominate in Bangladesh in the coming decades given the enormous exploratory task awaiting the taxonomists. It concludes that to put taxonomy in the sustainable development discourse, taxonomists must change their perception towards their role in the society and proactively share their work with wider audience. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17404 Bangladesh J. Plant Taxon. 20(2): 267-279, 2013